Psychological Impact of Online Learning during the COVID-19 Pandemic: A Case Study on Vocational Higher Education - Hutomo Atman Maulana (Indonesian Journal of Learning Education and Counseling, 2021)
This study aimed to determine the psychological impact in students due to online learning in vocational higher education conducted during the Corona virus disease 2019 (Covid-19). The samples in this study were all the students of the Undergraduate Program Department of Commercial Administration of Politeknik Negeri Bengkalis. The Samples were taken using the purposive sampling technique focused solely on students who gained online learning in theory and Practice courses since the use of online learning because of the COVID-19. The Data was collected using a DASS 42 instrument through online questionnaire. The results of this study showed that online learning in the higher education of psychologically impactful, which resulted in 29% of students having a level of depression above normal, 70% of students had an anxiety level above normal, and 46% of students had a stress level above normal.